2021
DOI: 10.1186/s12284-021-00455-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rice Transcriptome Reveals the LncRNA/CircRNA Regulation in Tissue Development

Abstract: Background Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) can play important roles in many biological processes. However, no study of the influence of epigenetics factors or the 3D structure of the genome in their regulation is available in plants. Results In the current analysis, we identified a total of 15,122 lncRNAs and 7902 circRNAs in three tissues (root, leaf and panicle) in the rice varieties Minghui 63, Zhenshan 97 and their h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…To understand the translation ability of widely distributed lncRNAs reported in our previous work (Zhou et al ., 2021), we re-identified the lncRNAs in MH63RS3 genome with the same pipeline and predicted their coding potential. In total, only 4.95% (668) of all lncRNAs with one or more active ORFs could be translated (Figure 4A, Data S4), suggesting that the identification of a majority of lncRNAs in our previous study is reliable and the translation of lncRNAs is not universal in rice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the translation ability of widely distributed lncRNAs reported in our previous work (Zhou et al ., 2021), we re-identified the lncRNAs in MH63RS3 genome with the same pipeline and predicted their coding potential. In total, only 4.95% (668) of all lncRNAs with one or more active ORFs could be translated (Figure 4A, Data S4), suggesting that the identification of a majority of lncRNAs in our previous study is reliable and the translation of lncRNAs is not universal in rice.…”
Section: Resultsmentioning
confidence: 99%
“…Five types of lncRNAs were previously classified and we found that 60.3% of active ORFs were derived from long intergenic noncoding RNAs (lincRNAs), followed by long noncoding natural antisense transcripts (lncNATs; 23.4%; Figure 4C). Considering the poor conservation of lncRNAs among varieties (Zhou et al ., 2021), and the relatively large number of shared active translational ORFs among varieties and tissues (Figure S5A), we speculate that these lncRNAs may have similar functions to protein-coding genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some plant species represented the remarkable proportion of TE-lncRNAs. For instance, 65% of Zea mays lncRNAs (Lv et al, 2019) and 53% of Oryza sativa lncRNAs (Zhou et al, 2021) contained sequences that appear to be derived from TEs. On the other hand, some plant species, such as Brachypodium distachyon with 8% (De Quattro et al, 2017), Aegilops tauschii with 19%, and Triticum urartu with 27% (Pieri et al, 2018), exhibited less proportion of lncRNAs which can be attributed to TEs.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic sequencing can be used to sequence almost all transcripts in specific biological tissues or cells at a certain period. Additionally, it can be applied to study gene expression, structure, variable splicing and to predict new transcription ( Patel et al, 2021 ; Sun et al, 2021 ; Wang et al, 2021 ; Zhou et al, 2021 ). Fei et al (2020) employed transcriptome sequencing and RT-qPCR to determine the expression levels of 20 genes related to fatty acid synthesis in Zanthoxylum bungeanum seeds, the results of intergroup correlation and RDA analysis suggested that ENR , ECR , and SAD1 are the key genes in fatty acid synthesis.…”
Section: Introductionmentioning
confidence: 99%